Kinetics of Nanoparticles Nucleation/Growth and Control of the Pt/C Catalysts Microstructure and Activity. Issue 1 (1st February 2022) - Danilenko, M.; Guterman, V.; Paperzh, K.; Alekseenko, A.; Nikulin, A.
Abstract: A kinetic analysis of the complex Pt(IV) ions reduction has been carried out for two common liquid-phase synthesis methods, in which formaldehyde and formic acid are used as reducing agents. The character of the influence of temperature, the nature of the reducing agent and solution components, the atmosphere composition, and the carbon support have been established. This made it possible to optimize the synthesis conditions and obtain Pt/C catalysts with ultrasmall nanoparticles, significantly exceed commercial analogs in their morphology, durability, and activity in the oxygen electroreduction reaction.